Haskalah : the romantic movement in Judaism - Litvak, Olga (Key words in Jewish studies, 2012)
"Commonly translated as the "Jewish Enlightenment," the Haskalah propelled Jews into modern life. Olga Litvak argues that the idea of a Jewish modernity, championed by adherents of this movement, did not originate in Western Europe's age of reason. Litvak contends that the Haskalah spearheaded a Jewish cultural revival, better understood against the background of Eastern European Romanticism. Based on imaginative and historically grounded readings of primary sources, Litvak presents a compelling case for rethinking the most important concepts that currently inform the positioning of the Haskalah within the context of Jewish emancipation, nationalism, and secularization. Most importantly, she challenges the prevailing view that the Haskalah was the political and philosophical mainspring of Jewish liberalism. In Litvak's ambitious rereading, nineteenth-century Eastern European intellectuals emerge as the authors of a Jewish Romantic revolution. Fueled by unfulfilled longings for community, spiritual perfection, and historical authenticity, the poets and scholars associated with the Haskalah were ambivalent about the contemporary struggle for Jewish equality and the quest for material improvement. Their skepticism about the universal promise of Enlightenment continues to shape Jewish political and religious values."--Project Muse.